Survival of Wild Adults of Ceratitis capitata (Wiedemann) under Natural Winter Conditions in North East Spain - E. Peñarrubia-María; J. Avilla; L. A. Escudero-Colomar (Psyche: A Journal of Entomology)
The overwintering of the Mediterranean fruit fly (medfly), Ceratitis capitata (Wiedemann) at the northern limits of its geographic distribution is not yet well known. With the aim of estimating the survival rate of medfly adults in northeast Spain under natural winter conditions, a two-winter-season trial was carried out. A control was carried out in a climatic chamber at 25°C. The results showed that medfly adults were unable to survive the entire winter season in the Girona area. Climatic conditions, including the daily minimum temperature, daily maximum temperature and the high rainfall, appeared to be involved in adult mortality in winter.